Degree of Trauma Differs for Major Osteoporotic Fracture Events in Older Men Versus Older Women. (3rd August 2015) - Ensrud, Kristine E; Blackwell, Terri L; Cawthon, Peggy M; Bauer, Douglas C; Fink, Howard A; Schousboe, John T; Black, Dennis M; Orwoll, Eric S; Kado, Deborah M; Cauley, Jane A; Mackey, Dawn C; ,
ABSTRACT: To examine the degree of trauma in major osteoporotic fractures (MOF) in men versus women, we used data from 15, 698 adults aged ≥65 years enrolled in the Osteoporotic Fractures in Men (MrOS) study (5994 men) and the Study of Osteoporotic Fractures (SOF) (9704 women). Participants were contacted tri‐annually to ascertain incident fractures, which were confirmed by radiographic reports and coded according to degree of self‐reported trauma. Trauma was classified as low (fall from ≤ standing height; fall on stairs, steps, or curb; minimal trauma other than fall [coughing, turning over]); moderate (collisions with objects during normal activity without associated fall); or high (fall from > standing height; severe trauma [motor vehicle accident, assault]). MOF included hip, clinical vertebral, wrist, and humerus fractures. Mean fracture follow‐up was 9.1 years in SOF and 8.7 years in MrOS. A total of 14.6% of the MOF in men versus 6.3% of the MOF in women were classified as high trauma ( p < 0.001); men versus women more often experienced fractures resulting from severe trauma as well as from fall > standing height. High‐trauma fractures were more significantly common in men versus women at the hip ( p = 0.002) and wrist ( p < 0.001) but not at the spine or humerus. Among participants with MOF, the odds ratio of a fracture related to high‐trauma fracture among men versus women was 3.12 (95% confidence interval [CI] 1.70–5.71) after adjustment for traditional risk factors. Findings were similar in analyses limited to participants with hip fractures (odds ratio [OR] = 3.34, 95% CI 1.04–10.67) and those with wrist fracture (OR = 5.68, 95% CI 2.03–15.85). Among community‐dwelling older adults, MOF are more likely to be related to high trauma in men than in women. These findings are not explained by sex differences in conventional risk factors and may reflect a greater propensity among men to engage in risky behavior. © 2015 American Society for Bone and Mineral Research.